-8u-7+2u=33

Simple and best practice solution for -8u-7+2u=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8u-7+2u=33 equation:


Simplifying
-8u + -7 + 2u = 33

Reorder the terms:
-7 + -8u + 2u = 33

Combine like terms: -8u + 2u = -6u
-7 + -6u = 33

Solving
-7 + -6u = 33

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -6u = 33 + 7

Combine like terms: -7 + 7 = 0
0 + -6u = 33 + 7
-6u = 33 + 7

Combine like terms: 33 + 7 = 40
-6u = 40

Divide each side by '-6'.
u = -6.666666667

Simplifying
u = -6.666666667

See similar equations:

| 23=3y+2 | | (X-12)-2x=3x+4 | | v/5-3=2 | | 4+3v=-2 | | 10t^3+13t-3=0 | | 0.0003x^2+0.1x-88=0 | | 6x-(2x+1)=19 | | 4x^2-9y^2+16x+54y-29=0 | | y=1E+7x+-0.11 | | (331/5)-(331/6)=X | | n(n-2)=8 | | 7z^2-z-8=0 | | (X-5)/(X-6)=56 | | (X-5)(X-6)=56 | | 5x^4/10 | | 1000x^2-100x=0 | | 6x+2y+3y=11 | | (D^4+4D^2)y=96x^2 | | 2x11/4=13 | | (5.6x+2)(5.6x-2)= | | 25x^2+9y^2-18y-216=0 | | (0.6x-1.28)(18x+8)= | | 72=4x-12 | | 2m(n+3)-m(2n+1)= | | 2e^x/8e^-x | | X+0.6x=250y | | -5x+10=14+(4+x) | | g+7f=16 | | 12=3*x | | 4x^2+x=44 | | 9x+-9y=27 | | f(x)=10x-18 |

Equations solver categories